1996
DOI: 10.1016/0029-7844(96)00316-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of ovarian stromal blood flow at the baseline ultrasound scan to subsequent follicular response in an in vitro fertilization program

Abstract: Ovarian stromal blood flow at the baseline ultrasound scan is correlated with subsequent follicular response and may be a new indicator for predicting ovarian responsiveness in an IVF program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 22 publications
2
61
1
6
Order By: Relevance
“…A number of studies have showed a relationship between ovarian stromal blood flow early in the cycle and the ovarian responsiveness (11,(26)(27)(28)(29). A lower IOA PI early in the cycle (day 2 or 3) is associated with a larger number of growing follicles (11) and a larger number of oocytes retrieved (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have showed a relationship between ovarian stromal blood flow early in the cycle and the ovarian responsiveness (11,(26)(27)(28)(29). A lower IOA PI early in the cycle (day 2 or 3) is associated with a larger number of growing follicles (11) and a larger number of oocytes retrieved (29).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Bassil et al (27) demonstrated that a lower IOA RI two days before HMG injections started is associated with an increased oocyte retrieval rate. A number of studies have shown that IOA PSV assessed on day 3 (26) or on the day of downregulation (28) is significantly lower in poor responders.…”
Section: Discussionmentioning
confidence: 99%
“…Gonadotropin stimulation was commenced upon confirmation of pituitary quiescence with a concomitant reduction in the dose of buserelin to 200 µg/day. Recombinant follicle stimulating hormone (FSH), Gonal-F ® (Serono Canada Inc, Ontario Canada) or Puregon ® (Organon Canada Ltd, Ontario Canada) were started as a dose on the basis of woman's age, antral follicle count, basal FSH concentrations, and intraovarian stromal blood flow (20). Human chorionic gonadotropin (hCG) (Profasi ® , Serono Canada Ltd), 10,000 IU was administered subcutaneously when at least three follicles ≥18 mm in diameter were observed.…”
Section: Methodsmentioning
confidence: 99%
“…Possible markers include female age, early follicular serum FSH (18), estradiol and inhibin B concentrations (19), and ultrasonographic parameters including ovarian volume (20), antral follicle count (21), and peak ovarian stromal blood flow velocity (7). Further work is required on selecting stimulation protocols and appropriate starting doses of gonadotropins for women identified to be at increased risk of poor ovarian response.…”
Section: Discussionmentioning
confidence: 99%
“…The same starting dose may be used for all women, or the starting dose can be individualized based on predictors of ovarian response such as female age, early follicular phase serum FSH concentration (5), ultrasonographic criteria (3,6,7) and previous follicular response to ovarian stimulation. Subsequently, the dose may be held constant throughout stimulation, increased or decreased in a fixed manner, or titrated according to the ovarian response.…”
Section: Introductionmentioning
confidence: 99%